2023
DOI: 10.1177/17588359231183679
|View full text |Cite
|
Sign up to set email alerts
|

Antibody–drug conjugates: the evolving field of targeted chemotherapy for breast cancer treatment

Abstract: Antibody–drug conjugates (ADCs) are a class of antineoplastic agents whose structure is composed of three main components: a monoclonal antibody (mAB) targeting a specific target antigen, a cytotoxic payload, and a linker binding the antibody to the payload. By combining the specificity of mABs with the high potency of the payloads, ADCs constitute a smart drug delivery system with improved therapeutic index. After recognition and binding of the mAB to its target surface antigen, ADCs are internalized by endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…The ADC is administered into the blood, where the antibody component binds to cancer-specific surface antigens. Endocytosis of the ADC releases the cytotoxic payload, which disrupts DNA regulatory proteins and causes cancer cell death [30]. A challenge in designing ADCs is the trade-off between antigen affinity and tumor penetration.…”
Section: Advances In Development and Emerging Treatmentsmentioning
confidence: 99%
“…The ADC is administered into the blood, where the antibody component binds to cancer-specific surface antigens. Endocytosis of the ADC releases the cytotoxic payload, which disrupts DNA regulatory proteins and causes cancer cell death [30]. A challenge in designing ADCs is the trade-off between antigen affinity and tumor penetration.…”
Section: Advances In Development and Emerging Treatmentsmentioning
confidence: 99%
“…ADCs bring together the targeting advantages of monoclonal antibodies (mAbs) with the cytotoxic potential of small molecules to enhance specific drug delivery in tumor cells through the antibody-antigen interaction while sparing healthy tissues and/or cells from toxic damage 6 , 7 , 8 . Once mAbs selectively bind to the target antigen on the tumor cell, ADCs are internalized into cells and the payloads are released with the linker breaking or antibody hydrolysis, followed by free drug disrupting the function of the corresponding cellular structure 9 . The clinical results of ADCs are undeniably encouraging and preferable ADCs are designed continuously, but they still have shortcomings, including low drug loading capacity, poor delivery efficiency, possible immunogenicity, high cost of ADCs production, and low potential to penetrate solid tumors 10 , 11 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…T-DM1 has low payload membrane permeability and is bound by a thioether non-cleavable linker, while T-DXd has high payload membrane permeability and is bound by a cleavable tetrapeptide-based linker. Between the two, only T-DXd presents the bystander effect [24] that leads to cell death of the neighboring tumor cells by amplifying the activity of the cytotoxic drug [25] (Figure 2b). Regarding their efficiency, a study performed by Cortes et al showed that the risk of disease progression or death was reduced in patients treated with T-DXd compared to T-DM1 [29].…”
Section: Introductionmentioning
confidence: 99%